2009
DOI: 10.1073/pnas.0902745106
|View full text |Cite
|
Sign up to set email alerts
|

IL-1 acts directly on CD4 T cells to enhance their antigen-driven expansion and differentiation

Abstract: cytokines ͉ inflammasome ͉ Th1 ͉ Th17 ͉ Th2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
436
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 497 publications
(466 citation statements)
references
References 32 publications
21
436
1
8
Order By: Relevance
“…First, it has been widely reported that IL-1 signaling is required for T H 2-mediated immunity and allergy (36)(37)(38)(39). More specifically, IL-1 signaling is required to activate T H 2 cells directly in vivo (13,40). Second, a relationship between IL-1R/ubiquitin C and Trim24 has been suggested previously (15-19); however, the requirement of Trim24 for IL-1R expression has not been reported.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…First, it has been widely reported that IL-1 signaling is required for T H 2-mediated immunity and allergy (36)(37)(38)(39). More specifically, IL-1 signaling is required to activate T H 2 cells directly in vivo (13,40). Second, a relationship between IL-1R/ubiquitin C and Trim24 has been suggested previously (15-19); however, the requirement of Trim24 for IL-1R expression has not been reported.…”
Section: Resultsmentioning
confidence: 89%
“…In line with this prediction, IL-1R signaling is required for T H 2-dependent immunity (36,37) and T H 2-mediated airway allergy (38,39), supporting observations presented here with Trim24 −/− T cells. Specifically, IL-1 signaling is required to activate T H 2 cells in vivo (13,40), and, as we show here, IL-1R signaling in T cells can exacerbate T H 2-driven airway allergy. In support of this upstream mechanistic link, Tim24 −/− T H 2 cells were refractory to IL-1β-induced activation/proliferation and cytokine production in vitro, and mice with Tim24 −/− T cells failed to develop exacerbated disease when activated with allergen and IL-1β.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Em síntese, a IL-1β e a IL-18 agem em linfócitos de diferentes formas como através da expressão do receptor para IL-2R e assim, prolongando a sobrevivência destas células, assim como aumentando a proliferação e diferenciação de linfócitos B (BEN-SASSON et al, 2009;MALISZEWSKI et al, 1990). Em adição, a IL-1β e a IL-18 atuam no desvio e amplificação da resposta Th17 e Th1, respectivamente (CHUNG et al, 2009;GUO et al, 2009;HATA et al, 2004).…”
Section: Evidências Do Papel De Nlrs Na Autoimunidadeunclassified